MAIN DIRECTIONS OF MODERN HUMANITIES PEDAGOGY (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the substance of concepts "humanism", "pedagogical direction". The different directions of humanistic pedagogic are analyzed.